Sequence and analysis of genomic sequences upstream of mei-3. - Richard Cheng; R. J. Radloff (Fungal Genetics Reports, 1994)
he Neurospora crassa mei-3 mutation causes sensitivity to various DNA damaging agents (Newmeyer and Galeazzi 1977 Genetics 85:461-487). We have recently cloned and mapped a genomic fragment capable of transforming mei-3 spheroplasts to wild type (Cheng et al. 1993 Mut. Res. 294:223-234). These experiments predicted the putative coding sequence of mei-3 or at least the region encompassing the mei-3 mutation. It was determined by homology that Mei-3 belongs to the RecA-like group of proteins (Bishop et al. 1992 Cell 69:439-456) which are intimately involved in the recombination process and had been previously identified only in prokaryotes. Since the identification of RecA-like proteins in Saccharomyces (Shinohara et al. 1992 Cell 69:457-470) and in Neurospora, our hypothesis that this important group of proteins may be highly conserved in other eukaryotes has been substantiated with the cloning of several Rec-A like proteins from mouse, chicken, lily, and human (Shinohara et al. 1993 Nat. Genet. 4:239-243). Using these data there is evidence that additional homology, upstream of our putative start site, to these other proteins exists (an additional 67% over 39 amino acids between Mei-3 and mouse Rad51: Figure 1). However, this region of homology lacks a start site or obvious splice sites. This might suggest the presence of an unidentified upstream start sequence and another exon without obvious splice sequences. In an attempt to address this possibility, we sequenced both strands of the previously unpublished genomic sequence, from -2519 to -271 bp upstream of the putative 5' end of mei-3.